2014
DOI: 10.1542/peds.2013-3787
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Comorbidities in Children With Active Epilepsy: A Population-Based Study

Abstract: BACKGROUND: In addition to recurrent epileptic seizures, children with epilepsy can have coexisting cognitive and behavioral difficulties but the spectrum and prevalence of such difficulties are uncertain. METHODS: The Children with Epilepsy in Sussex Schools study is a prospective, community-based study involving school-aged children (5–15 years) with active epilepsy in a defined geographical area in the United Kingdom. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
213
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(247 citation statements)
references
References 29 publications
13
213
4
8
Order By: Relevance
“…Our data on the risk of ASD in individuals with epilepsy are consistent with earlier studies, [3][4][5] although previous risk estimates have varied substantially. One American study based on hospital health care data reported an OR of more than 22 for the association between ASD and epilepsy.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Our data on the risk of ASD in individuals with epilepsy are consistent with earlier studies, [3][4][5] although previous risk estimates have varied substantially. One American study based on hospital health care data reported an OR of more than 22 for the association between ASD and epilepsy.…”
supporting
confidence: 89%
“…A US study of health care data, a British psychiatric morbidity survey, and a prospective screening study all found that ASD as a comorbidity in patients with epilepsy had a prevalence between 1.3% and 21% and an odds ratio (OR) between 6 and 22. [3][4][5] Prevalence of epilepsy in ASD has been studied in different large cohorts with results varying from 3.9% to 19.4%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The epilepsy associated comorbidities are often underestimated, consequently, undertreated. Furthermore, cognitive deficits always remain despite seizure greatly control [9]. Increased attention and early management of associated comorbidities is of great significance to improve the quality of life and maximize the opportunity for patients to re-integrate the society.…”
Section: Introductionmentioning
confidence: 99%
“…По данным проведенного в Вели-кобритании популяционного исследования CESS (Children with Epilepsy in Sussex Schools) с примене-нием современных диагностических инструментов (Diagnostic and statistical manual of mental disorders IV, DSM-IV), у 80 % детей были выявлены поведенческие и / или когнитивные нарушения, у 40 % -интеллекту-альные нарушения, у 33 % -СДВГ, у 21 % -аутисти-ческое расстройство [67].…”
unclassified